Refining Ethical Reflections in Cybersecurity Policy and Privacy: Insights for Policy Makers - Ryma Abassi (Journal of Universal Computer Science)
As governments and organizations seek to strengthen cybersecurity measures, ethical considerations play a crucial role in shaping effective and responsible policies. This research article explores the ethical dimensions of cybersecurity policymaking, focusing on the balance between security imperatives and individual privacy rights. Drawing on principles of ethics, human rights, and legal frameworks, the article discusses challenges and dilemmas faced by policymakers in ensuring cybersecurity without compromising privacy and civil liberties. It proposes a set of ethical guidelines and best practices for designing and implementing cybersecurity policies that are both effective and respectful of fundamental rights and values.